2010
DOI: 10.1186/1471-2229-10-205
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of the Lemnaceae, a family of aquatic monocots

Abstract: BackgroundMembers of the aquatic monocot family Lemnaceae (commonly called duckweeds) represent the smallest and fastest growing flowering plants. Their highly reduced morphology and infrequent flowering result in a dearth of characters for distinguishing between the nearly 38 species that exhibit these tiny, closely-related and often morphologically similar features within the same family of plants.ResultsWe developed a simple and rapid DNA-based molecular identification system for the Lemnaceae based on sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
155
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(168 citation statements)
references
References 33 publications
9
155
2
2
Order By: Relevance
“…A chemotaxonomic study of the genus Wolffiella including W. caudata was performed by based on the allozyme profiles. Barcoding (Wang et al, 2010;Borisjuk et al, 2015) and a detailed molecular taxonomic investigation of this species based on AFLP and plastidic marker sequences (unpublished data; Bog, Sree and Appenroth) has been carried out recently together with other species of the genus Wolffiella. These investigations further support its species identity.…”
Section: Newly Discovered Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A chemotaxonomic study of the genus Wolffiella including W. caudata was performed by based on the allozyme profiles. Barcoding (Wang et al, 2010;Borisjuk et al, 2015) and a detailed molecular taxonomic investigation of this species based on AFLP and plastidic marker sequences (unpublished data; Bog, Sree and Appenroth) has been carried out recently together with other species of the genus Wolffiella. These investigations further support its species identity.…”
Section: Newly Discovered Speciesmentioning
confidence: 99%
“…Within the last three decades, quite a number of changes have been introduced to taxonomic classification of duckweeds in comparison to the published key. Moreover, molecular taxonomy and barcoding of duckweed species (Wang et al, 2010;Bog et al, 2010Bog et al, , 2013Bog et al, , 2015Borisjuk et al, 2015) has made huge progress and it aids in identification of duckweed species. However, it is not practically and economically viable to determine each of the collected duckweed clones by Amplified Fragment Length Polymorphism (AFLP) or by sequencing of DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reactions (PCR) were performed with the following primer pairs (5′ to 3′): ATGTCACCACAAACAGAGACTAAAGC and GTAAAATCAAGTCCACCRCG (Wang et al 2010) for the rbcL gene and TTATGCATGAACGTAATGCTC and CGCGCATGGTGGATTCACAATCC (Tate and Simpson 2003) for the psbA-trnH spacer region. The reaction mixture (30 μl) consisted of GoTaq Green Master Mix (Promega), 0.5 μM primers, and 10 ng DNA template.…”
Section: Amplification Of the Dna Fragments Of Rbcl And Psba-trnh Spamentioning
confidence: 99%
“…The performance of DNA barcoding has, however, been mixed for various plant taxa: while some limitations have been documented in some groups e.g. Viburnum (Adoxaceae; Clement and Donoghue 2012), Agalinis (Orobanchaceae; Pettengill and Neel 2010), Tetrastigma (Vitaceae; Fu et al 2011), Lemnaceae (Wang et al 2010), Berberis (Berberidaceae; Roy et al 2010), and Parnassia (Parnassiaceae; Yang et al 2012), strong and reliable performance of DNA barcodes has also been reported in many other studies of specimen identification (Burgess et al 2011;Gere et al 2013;Mankga et al 2013). …”
Section: Introductionmentioning
confidence: 99%